PELAKSANAAN GERAKAN MAGRIB MENGAJI BAGI ANAK-ANAK DI DUSUN III DESA LUBUK ROTAN KECAMATAN PERBAUNGAN - Asnaida; Ainun Azzahra; Khoirunnisa; Mhd Helmi Lubis (STAI Nurul Falah Airmolek, 2025)
This study examines the implementation of the Maghrib Mengaji Movement in Hamlet III of Lubuk Rotan Village, Perbaungan District, Serdang Bedagai Regency. This program is carried out routinely every day after the Maghrib prayer with the aim of increasing children's faith and ability to read the Quran through learning methods such as iqra' and questions and answers at the mosque and the Quran teacher's house. The results of the study indicate that this activity received support from the community and local religious leaders, despite facing obstacles such as inadequate facilities, less than optimal parental motivation, and children's interest that needs to be improved. In general, this program has a positive impact by increasing children's interest in learning the Quran and fostering their religious enthusiasm. It is recommended that parents be more active in providing supervision and motivation in a friendly and consistent manner, so that children can enjoy the learning process and develop a strong Islamic character. The implementation of this program is expected to be able to shape a generation with noble morals and a strong Islamic personality, as well as provide long-term benefits in children's religious education. Kata Kunci: Pelaksana,Gerakan,Magrib Mengaji, Anak-Anak.